Do Marketing Margins Change with Food Scares? Examining the Effects of Food Recalls and Disease Outbreaks in the U.S. Red Meat Industry. Issue 4 (10th April 2013) - Capps, Oral; Colin‐Castillo, Sergio; Hernandez, Manuel A.
ABSTRACT This study examines the impact of different food scare events on marketing margins in the U.S. beef and pork industries. The authors analyze how market stresses induced by the Food Safety Inspection Service (FSIS) recalls and bovine spongiform encephalopathy (BSE) outbreaks affect price spreads and the extent of price transmission at the slaughter‐to‐wholesale and wholesale‐to‐retail levels. They use monthly national data for the period 1986–2008, which includes records of FSIS recalls of varying severity and BSE events in the United States and Canada. The authors account for immediate and delayed effects of food scares and for potential cross effects across industries and countries. The results indicate that beef and food recalls do not affect their corresponding price margins and overall food safety incidents have minor cross‐industry and cross‐country effects. However, BSE discoveries in the United States considerably affect marketing margins in the beef industry, particularly at the wholesale‐to‐retail level. Interestingly, subsequent discoveries had smaller impacts on price margins. Bovine spongiform encephalopathy outbreaks also appear to affect the extent of price transmission between wholesalers and retailers.